Mechanical properties of young mice tibia in four circumferential quadrants under nanoindentation. (November 2022) - Zhang, Guanjun; Li, Zhentao; Li, Na; Shi, Jian; Fan, Haonan; Mao, Haojie
Abstract: Characterizing the mechanical properties of different anatomical quadrants of bones has been conducted in the literature to help understand the correlations among bone morphometric, densitometric, and material properties. However, although there are data to compare four quadrants of the long bones of the adult, there is very limited research on the young adult especially young female. Hence, nine tibia mid-shaft specimens were harvested from nine 8-week-old C57BL/6J female mice, which roughly correspond to the age range of juvenile to young adult, with one left tibia being harvested from one animal. A total of 144 indentation tests were performed with four indentations per quadrant and each of nine tibia specimens being divided into four quadrants. The Oliver and Pharr methods were used to calculate the indentation modulus and hardness. One-way ANOVA and the Kruskal-Wallis nonparametric test were used to study the influence of different anatomical quadrants on the indentation modulus and hardness. The results showed that the indentation modulus of the 8-week-old mouse tibia shaft was 18.94 ± 0.91 GPa, and the hardness was 0.51 ± 0.02 GPa. The influence of circumferential anatomical quadrants on the tibial shaft indentation modulus ( p = 0.398) and hardness ( p = 0.895) was not statistically significant. These methods and results could potentially help study treatments for young female long bones by comprehensively understanding the effect of treatments on four quadrants, considering collagen fiber, the degree of mineralization, and the changes of collagen cross-linking through high-resolution nanoindentation.